Pengaruh Edible Coating berbasis Pati Singkong dan Suhu Penyimpanan terhadap Masa Simpan Tomat (Lycopersicum esculentum Mill.) - Tiara Arsyadita; Susiyanti Susiyanti; Ratna Fitry Yenny; Imas Rohmawati Imas Rohmawati (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The purpose of this study was to determine the effect of cassava starch concentration as a basic ingredient for edible coating and storage temperature on the shelf life of tomatoes (Lycopersicum esculentum Mill.). This study was conducted at the Plant Physiology and Biotechnology Laboratory, Faculty of Agriculture, Sultan Ageng Tirtayasa University in September 2024. Using a factorial Split-Plot Design with 2 factors and 3 replications, the first factor was the concentration of cassava starch (1.5%, 3%, 4.5%) and the second factor was storage temperature (25oC - 30oC, 10oC - 15oC). The data analysis process in this study used the Anova table and if the results of the analysis of variance showed significant to very significant differences, further testing was carried out. In this study, the Duncan Multiple Range Test (DMRT) will be used at the 5% level. Observations were carried out every 2 days for 14 days after the tomatoes were placed in storage, namely room temperature and low temperature. Observations were made on the variables, namely weight loss, fruit hardness, total dissolved solids (TPT), pH, and vitamin C. The results showed that the treatment of edible coating with cassava starch as the base material with a concentration of 3% had a significant effect on the weight loss parameter. The concentration of cassava starch of 1.5% also gave significantly different results on the fruit hardness parameter of 0.58N and vitamin C of 42.42%. The treatment of storage temperature showed that storage at low temperatures (10oC - 15oC) was better than storage at room temperature (25oC - 30oC) in maintaining weight and total loss of dissolved solids. There was an interaction between the concentration of cassava starch as the base material for edible coating and storage temperature on the parameters of total dissolved solids, fruit pH and vitamin C. Keywords: tomatoes, cassava starch, edible coating, storage temperature